Learning Innovation based on seTARA daring in the Community Learning Activity Center - Khoiruddin, M. Arif; Takhmid (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This study aims to describe learning innovations based on seTARA daring at (Community Learning Activity Center) PKBM Sunan Kalijaga Lirboyo Kediri, which includes planning, implementation, and evaluation stages, including identifying supporting and inhibiting factors and improvement efforts made. This study used a qualitative approach with a case study. In-depth interviews with leaders, teachers/tutors, and students, as well as observations of the learning process and online classes, were used to gain an in-depth understanding of experiences in the educational environment. Supporting data were obtained from official documents such as the e-learning curriculum, teaching records, and learning outcome evaluation. The results show that the learning innovation based on the seTARA daring application is practical and can benefit the students. At the planning stage, meetings were held to design implementation strategies, discuss policies, and announce the strategies and policies to students. The implementation stage involves implementing the policy and practical guidance and improving tutor innovation. The evaluation stage assessed the success of learning innovations based on the seTARA daring application by collecting feedback from tutors and students, becoming the basis for future improvement and enhancement. This research provides an essential contribution to understanding the challenges and potential solutions to optimize e-learning in the equivalency education program in PKBM.